(untitled) (Research, Society and Development, 2026)
Obstructive Sleep Apnea Syndrome (OSAS) is a respiratory disorder characterized by recurrent episodes of apnea and hypopnea during sleep, associated with partial or complete obstruction of the upper airways. These events result in intermittent hypoxia, sleep fragmentation, and sympathetic hyperactivation, triggering metabolic, cardiovascular, and neurocognitive repercussions that compromise quality of life. This study aimed to analyze the complexity of OSAS functioning in the human body, emphasizing sleep physiology, clinical consequences, and individualized therapeutic approaches. A narrative review of recent literature was conducted, including scientific articles published in recent years in indexed database. Findings demonstrate that the pathophysiology of OSAS is multifactorial, involving anatomical, neuromuscular, and metabolic alterations, in addition to factors such as obesity, aging, and the use of central nervous system depressants. Diagnosis is primarily based on polysomnography, complemented by home methods and emerging biomarkers. Regarding treatment, CPAP remains the gold standard, although alternatives such as oral devices, myofunctional therapies, lifestyle changes, surgeries, and new pharmacological approaches have gained prominence. Sleep hygiene has proven to be a relevant complementary resource, improving therapeutic adherence and symptoms. OSAS presents a complex clinical course and is associated with significant adverse outcomes. Effective management requires personalized therapeutic strategies, integrating both traditional and complementary resources. A broader understanding of its pathophysiology and the adoption of individualized approaches are essential to reduce complications, improve treatment adherence, and optimize patients’ quality of life.